2022
DOI: 10.1080/17476348.2022.2063843
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 patients require multi-disciplinary rehabilitation approaches to address persisting symptom profiles and restore pre-COVID quality of life

Abstract: Background: Long-COVID diagnosis is prominent, and our attention must support those experiencing debilitating and long-standing symptoms. To establish patient pathways, we must consider the societal and economic impacts of sustained COVID-19. Accordingly, we sought to determine the pertinent areas impacting quality of life (QoL) following a COVID-19 infection. Research methods: Three hundred and eighty-one participants completed a web-based survey (83% female, 17% male) consisting of 70 questions across 7 sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…The clinical characterisation and treatment of Long-COVID are complex [ 2 ] because there is a wide range of symptoms (most commonly fatigue and shortness of breath) with varying levels of severity [ 3 , 4 , 5 ]. Long-COVID is a growing burden upon global healthcare services with reports suggesting that over 144 million patients are living with multi-dimensional, episodic, and disabling symptoms that broadly impact functional status and quality of life [ 6 , 7 , 8 ]. It is currently predicted that 1 in 10 COVID-19 patients will develop Long-COVID, with some Western countries suggesting this could be as many as 1 in 6 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characterisation and treatment of Long-COVID are complex [ 2 ] because there is a wide range of symptoms (most commonly fatigue and shortness of breath) with varying levels of severity [ 3 , 4 , 5 ]. Long-COVID is a growing burden upon global healthcare services with reports suggesting that over 144 million patients are living with multi-dimensional, episodic, and disabling symptoms that broadly impact functional status and quality of life [ 6 , 7 , 8 ]. It is currently predicted that 1 in 10 COVID-19 patients will develop Long-COVID, with some Western countries suggesting this could be as many as 1 in 6 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings align with those of Davis et al [ 7 ], where patients experienced difficulties going back to their work; among those who did, many reported experiencing relapse and could no longer continue their work activities. Faghy et al [ 44 ] corroborated these results, with patients reporting reduced health and capacity to participate in daily and work activities. This highlights the importance of officials’ recognition of long COVID as a debilitating condition, hence offering those afflicted with it a proper recovery time before resuming their job.…”
Section: Discussionmentioning
confidence: 85%
“…49 Respiratory symptoms and severity following a COVID-19 infection are broad with mild upper respiratory tract symptoms such as a sore throat and cough regularly reported. 50 However, patients can develop more severe illness, commonly viral pneumonia, which can result in acute respiratory disorder syndrome (ARDS), which requires intense treatment and is linked to poor patient outcomes and/or mortality. 51 Whilst data on the short-term respiratory sequelae is still emerging, and longer-term follow-up studies remain scarce; 1370 pulmonary CT scans of 188 SARS-CoV2 patients identified the presence of pleural effusion, which was linked to increased risk of cardio-respiratory complications and hospital mortality.…”
Section: Respiratory Symptoms In Long Covidmentioning
confidence: 99%
“… 57 Arguably one of the most reported symptoms 3 months post-infection is chronic dyspnoea, with some data highlighting this as a key symptom in over half of the patients. 50 Chronic dyspnoea is associated with greater restriction on spirometry, lower pulmonary diffusing capacity, 55 reduced functional status, and greater desaturation during exertion than those without persistent dyspnoea, 58 suggestive of an underlying physiological mechanism that is responsible for this. Whilst the details of this have yet to be determined, early suggestions attribute pulmonary emboli 59 and potential vagus nerve dysfunction as possible explanations for various systemic symptoms, however more mechanistic insight is required.…”
Section: Respiratory Symptoms In Long Covidmentioning
confidence: 99%